Peningkatan Kompetensi Digital Siswa Sekolah Menengah Atas Melalui Pelatihan Koding dan Kecerdasan Buatan: Program Bina Talenta Indonesia - Ihsan Tanama Sitio; Danu Jaya Saputro; Muhammad Giriarda Abrari; Cepi Ramdani; Noer Fajrin (INTEGRATIF: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service program aimed to develop the potential of senior high school students in the fields of coding and artificial intelligence (AI). The hands-on training was conducted online via Zoom Meetings for synchronous sessions and an LMS for quizzes and exercises from September 15 to November 25, 2025. 60 senior high school students from 13 provinces across Indonesia participated and were divided into three classes. The results indicate that students’ knowledge increased substantially, as reflected in the improvement in mean test scores across all classes: from 54.87 to 83.13 in Class A, from 65.31 to 80.56 in Class B, and from 62.83 to 70.93 in Class C. The program demonstrated a significant positive impact, particularly in enhancing participants’ knowledge of artificial intelligence (AI) and coding, as well as their technical skills and character development.